2020
DOI: 10.2196/preprints.18725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient Challenges and Needs in Comprehending Laboratory Test Results: Mixed Methods Study (Preprint)

Abstract: BACKGROUND Patients are increasingly able to access their laboratory test results via patient portals. However, merely providing access does not guarantee comprehension. Patients could experience confusion or even anxiety when reviewing their test results. OBJECTIVE Our objective was to examine the challenges and needs that patients have when comprehending laboratory test results. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For example, the standard reference range of a laboratory test may not be applicable to older adults with chronic conditions [10]. Prior work has found that people often provided personal health information (eg, laboratory test results, age, medical history, and lifestyle) when posting questions on health forums to receive personalized recommendations from their peers [23,24]. From this perspective, providing information support tailored to the medical contexts of the patients could be very useful for them to determine whether results are worrisome and what might be appropriate for them to do.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the standard reference range of a laboratory test may not be applicable to older adults with chronic conditions [10]. Prior work has found that people often provided personal health information (eg, laboratory test results, age, medical history, and lifestyle) when posting questions on health forums to receive personalized recommendations from their peers [23,24]. From this perspective, providing information support tailored to the medical contexts of the patients could be very useful for them to determine whether results are worrisome and what might be appropriate for them to do.…”
Section: Motivationmentioning
confidence: 99%
“…When patients attempted to make sense of their results, they often turned to the internet to seek further information [23]. However, information on the web is sometimes either too general or misleading.…”
Section: Providing Pertinent and Reliable Information Tailored To The...mentioning
confidence: 99%